OPTIMALISASI PERAWATAN LIFE SAVING APPLIANCES (LIFEBOAT) GUNA MENINGKATKAN KESELAMATAN DI KAPAL MT. PASAMAN - Fahera, Nadella; Abadi, Kurniawan; Rizal Rochmansyah; Erlinda, Nelfi; Purba, Damayanto (STKIP Subang, 2026)
Life Saving Appliances (LSA) are essential safety equipment that play a vital role in ensuring crew safety, particularly in emergency situations. However, the maintenance of LSA on board ships is not always carried out optimally despite routine inspections. This study aims to identify problems in LSA maintenance, analyze factors contributing to suboptimal maintenance, and formulate efforts to optimize LSA maintenance, especially lifeboats, on board MT. Pasaman The data obtained are data collected from observations where researchers observe directly the object of research, documentation where research take pictures using a camera as a supporting, and interviews where researches ask questions directly to respondents and record respondents answer. This study uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using the 3M approach (Man, Money, Method) to identify factors affecting the implementation of LSA maintenance. The results show that lifeboat maintenance has been carried out in accordance with SOLAS, ISM Code, and the Planned Maintenance System (PMS) procedures. However, the implementation has not been fully optimal due to operational time constraints, uneven crew understanding, and inspections that are not conducted comprehensively. Optimization efforts can be achieved by improving supervision of maintenance activities, conducting regular safety meetings and drills, and adjusting maintenance schedules to ship operational activities to ensure the readiness of safety equipment.